Extracting terminology by language independent methods - Seljan, Sanja (Array, 2017)
Automatic extraction of corpus-based terminology can help in building terminology lists which represent valuable resource for the research, education and practical implementation. Specific terminology lists represent an intermediate step between the free text and the controlled vocabulary. Such lists can be used in information retrieval, in document indexing, in machine learning, in education, or extended to cross-language information access. Terminology extraction could be performed on monolingual or bilingual/ multilingual texts by . various terminology extraction methods relying on statistical or language approaches, or on hybrid model. Evaluation of extracted terminology candidates requires considerable human expertise in evaluation and final compilation. The paper presents automatic extraction process from monolingual text performed by three language independent tools, but relying on different principles. The research is conducted on the specific text domain relating to medical documentation consisting of reports, approvals and decisions on chemical and pharmaceutical documentation and instructions of use. After the digitization process and use of OCR techniques, the automatic extraction process is performed by use of three language independent tools. Results are compared and evaluated. Results are discussed in the frame of possible integration into more complex information system.